IMPLEMENTASI MANAJEMEN STRATEGIK DI LEMBAGA PENDIDIKAN (Studi Kasus di SMAN 1 Boyolangu) - zainul arifin; Agus Zaenul Fitri (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2023)
Abstract Strategic management can be defined as a series of management decisions and actions (planning, organizing, actuating, controlling) which are implemented by all organizational components in a series of achieving organizational goals that are desired. In strategic management, it includes at least three things, strategy formulation (strategy formulating), strategy implementation (strategy implementing), and strategy evaluation/control (strategy evaluating). In strategy formulation, there are five main steps of strategy formulation, namely 1) mission formulation, 2) external environment analysis, 3) internal organizational analysis, 4) formulation of specific objectives, and 5) strategy determination. keyword:implementasi strategic management